Edukasi Pemantauan Pertumbuhan Anak Balita pada Kader Posyandu di Puskesmas Wenang Kota Manado : (Education on Monitoring the Growth of Children Under Five at Posyandu Cadres at Puskesmas Wenang Kota Manado) - Nancy Malonda; Sulaemana Engkeng; Yulianty Sanggelorang (Sam Ratulangi University, 2024)
Monitoring children's growth is important to find out their nutritional status. This is useful for improving nutritional status if a child is found with poor nutritional status. One way to monitor the growth of babies and toddlers is by holding Posyandu. Active community participation is needed to support the achievement of the goals of Posyandu activities. Cadres are important people in Posyandu activities. Cadres who are active, agile, and knowledgeable can help in improving the nutritional status of infants and toddlers. The Wenang Community Health Center in the city of Manado has 28 Posyandu with an active cadre of around 63 people. In the last few years since the COVID-19 pandemic, cadres have not received socialization or assistance with anthropometric measurements and determining the nutritional status of toddlers. This activity aims to increase the knowledge and skills of Posyandu cadres regarding anthropometric measurements and assessing the nutritional status of toddlers. The type of method implemented is direct delivery in the form of counseling and training activities. The tools and materials used to support this activity are Child Growth Monitoring Charts, exposure materials, anthropometric measuring instruments, as well as pre-test and post-test questionnaires. Direct observations during the simulation were carried out to determine whether there was an increase in knowledge and skills in monitoring the growth of toddlers in Posyandu cadres. There is an increase in the knowledge and skills of Posyandu cadres for anthropometric measurements and assessing the nutritional status of toddlers in monitoring toddler growth. Success in monitoring the growth of children under five requires the Government's role and support for Posyandu through the Community Health Center and the Posyandu Operational Working Group (Pokjanal), to facilitate the implementation of various public health activities at Posyandu. Cadre Refreshing activities regarding monitoring the growth of toddlers are carried out routinely every year, facilitated by the Community Health Center. ABSTRAK Pemantauan pertumbuhan anak adalah hal penting untuk mengetahui bagaimana status gizinya. Hal ini berguna untuk memperbaiki status gizi apabila ditemukan anak dengan keadaan gizi yang tidak baik. Salah satu cara pemantauan pertumbuhan bayi dan balita adalah dengan diadakannya posyandu. Partisipasi aktif masyarakat diperlukan untuk menunjang tercapainya tujuan pada kegiatan posyandu. Kader merupakan orang penting dalam kegiatan posyandu. Kader yang aktif, cekatan, dan berpengetahuan luas dapat membantu keberhasilan dalam meningkatkan status gizi bayi dan balita. Puskesmas Wenang di kota Manado, memiliki 28 posyandu dengan jumlah kader aktif sekitar 63 orang. Dalam beberapa tahun terakhir sejak pandemi COVID-19 para kader belum mendapatkan sosialisasi maupun pendampingan pengukuran antropometri dan penentuan status gizi balita. Tujuan kegiatan ini untuk meningkatkan pengetahuan dan keterampilan kader posyandu mengenai pengukuran antropometri dan penilaian status gizi balita.Jenis metode yang dilaksanakan adalah penyampaian secara langsung berupa kegiatan penyuluhan dan pelatihan. Alat dan bahan yang digunakan dalam menunjang kegiatan ini adalah Grafik Pemantauan Pertumbuhan pada Anak, bahan paparan, alat ukur antropometri, serta kuesioner pre test dan post test. Pengamatan langsung saat simulasi dilakukan untuk mengetahui adanya peningkatan pengetahuan dan keterampilan dalam pemantauan pertumbuhan balita pada kader posyandu. Ada peningkatan pengetahuan dan keterampilan kader posyandu untuk pengukuran antropometri dan penilaian status gizi balita dalam pemantauan pertumbuhan balita.Keberhasilan dalam pemantauan pertumbuhan Balita, diperlukan peran dan dukungan Pemerintah kepada Posyandu melalui Puskesmas dan Kelompok Kerja Operasional (Pokjanal) Posyandu, untuk memfasilitasi pelaksanaan berbagai kegiatan kesehatan masyarakat di Posyandu. Kegiatan Refreshing Kader tentang pemantauan pertumbuhan Balita dilakukan rutin setiap tahun, dengan difasilitasi oleh Puskesmas.